MULTI CRITERIA ANALYSIS FOR PLANNING AND MANAGEMENT OF ECOSYSTEMS IN EASTERN COAST OF BINTAN ISLAND, INDONESIA - Prihanto, Yosef (Badan Informasi Geospasial in Partnership with MAPIN, 2009)
The Eastern Coast of BintanIslandis rich in resources and biodiversity that are potential for tourism commodity. As a coastal area, this area has also risks from environment damages that can degrade its potency and quality. A master plan is much needed to fulfill all interests. In practice the making of a master plan is not a simple process. The different aspects involved between the land and the sea that are bounded by administrative boundary but the ecosystem cannot be bounded in the same way are often found in every parts of coastal area. A method of analysis is developed to combine both land and sea factors into a single figure or scoring system that can be compared one another for the decision making. The use of remote sensing and geographic information technology support the analysis as well as surveys from the local knowledge. Keywords: coatal aea, integration, GIS, remote sensing. ABSTRAK Pantai Timur Bintan merupakan daerah yang kaya akan sumberdaya alam dan keanekaragaman hayati, yang potensial untuk komoditas pariwisata. Sebagai sebuah pesisir, daerah ini juga beresiko terhadap kerusakan lingkungan yang tentunya menurunkan potensi maupun kualitas lingkungannya. Sebuah master plan harus dibuat untuk memfasilitasi semua pihak yang berkepentingan. Dalam prakteknya hal ini tidaklah sederhana. Aspek-aspek yang berbeda melibatkan daratan dan lautan yang dibatasi oleh batas administrasi, tetapi ekosistem tidaklah demikian. Sebuah cara dikembangkan untuk menggabungkan komponen daratan dan lautan yang dapat dibandingkan satu sama lain dengan metoda skoring untuk pengambilan keputusan. Penggunaan citra satelit dan sistem informasi geografis membantu dalam analisa yang juga didukung dengan survei lapangan menggunakan pengetahuan lokal. Kata kunci: wilayah pesisir, integrasi, SIG, penginderaan jauh